PEMBUATAN LEGAL OPINION DALAM PENANGANAN PELANGGARAN ADMINISTRASI PEMILU TAHUN 2024 DI BAWASLU - Supriyadi, Supriyadi; Purnamasari , Andi Intan; Sulbadana , Sulbadana; Kasim , Aminuddin; M Yunus , Nursiah; Awaliyah , Awaliyah (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2023)
Since the previous election, the issue of electoral violations has become an inevitable problem. Almost every stage of the elections leaves the issue of violations dealt with by the Bawaslu of Parigi Moutong district, which allows them to make legal analysis and legal opinions. Basically, legal opinions are made to solve a particular problem. Clients often raise this problem. Therefore, a Legal Opinion should be made carefully, orderly, and proportionate. Besides, it has to be systematic in order to be understandable. Although there is no standard format for Legal Opinions, a minimum LO consists of: (1) Fact, (2) Issue, (3) Rules, (4) Application, and (5) Conclusion